Experiences with a solid tungsten divertor in ASDEX Upgrade. (August 2017) - Herrmann, A.; Zammuto, I.; Balden, M.; Greuner, H.; Jaksic, N.; Kallenbach, A.; Li, M.; Neu, R.; Rohde, V.; ,
Highlights: ASDEX Upgrade – a full tungsten experiment with a solid tungsten outer divertor. Significant differences in the target behaviour between high heat flux tests and plasma operation. 2 successful campaigns of plasma operation with a solid tungsten divertor despite cracks and leading edges. Abstract: In 2013 a redesigned solid tungsten divertor, Div-III, was installed in ASDEX Upgrade. In two experimental campaigns more than 2700 plasma discharges with up to 10 s duration, 110 MJ plasma heating, and reaching a P sep /R of 10 MW/m were conducted. Div-III is an adiabatically loaded divertor with tungsten target tiles clamped onto a water cooled structure. The tungsten target tiles were inspected and characterized during the shut-down period in 2014. As a result of the target inspection characteristic modifications of the plasma exposed tiles were detected that were not found during the target qualification in a high heat load test facility. 126 out of 128 tiles reveal deep cracks through the target. A lot of tiles show shallow cracks in the high heat load region and finally protruding tiles with strong local damages were found. It should be noted that none of these target damages have caused an unscheduled opening of ASDEX Upgrade.